Impact of non - invasive prenatal testing on prenatal diagnosis at Da Nang Hospital for women and children - Son, Pham Minh; Kong, Pham Chi; Suong, Tran Hoang; Vuong, Mai Thi Minh; Vinh, Tran Dinh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Non-invasive prenatal testing (NIPT) is being applied more widely in Vietnam. However, the effects of NIPT on prenatal diagnosis have not been studied much in our country. This study aims to analyze the impact of NIPT on the changes in the number of routine screening tests for chromosomal abnormalities 21, 18, and 13 and the impact of NIPT on invasive prenatal diagnostic procedures and propose strategies to screen for fetal aneuploidy. Results: NIPT did not change the number of routine screening tests for chromosomal abnormalities 21, 18, and 13. The rate of amniocentesis used to confirm the diagnosis of aneuploidy was decreased by 6,32 (p < 0,0001, 95% CI: 3,99 – 10,45). Among the strategies to detect aneuploidy 21, 18, and 13 suitable for socio-economic conditions in Vietnam, a 2-step screening method can be applied. Conclusions: NIPT did not change the number of routine screening tests. NIPT reduced the number of invasive prenatal procedures. The screening strategy for fetal aneuploidy should follow a two-step approach.